2018
DOI: 10.1523/eneuro.0407-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Theta Oscillations Promote Selective Encoding of Behaviorally Relevant Events

Abstract: The ability to capture the most relevant information from everyday experiences without constantly learning unimportant details is vital to survival and mental health. While decreased activity of the medial prefrontal cortex (mPFC) is associated with failed or inflexible encoding of relevant events in the hippocampus, mechanisms used by the mPFC to discern behavioral relevance of events are not clear. To address this question, we chemogenetically activated excitatory neurons in the mPFC of male rats and examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 83 publications
2
17
0
Order By: Relevance
“…In trace eyeblink conditioning, chemogenetic activation of excitatory neurons in the prelimbic region enables rats to associate a neutral stimulus and eyelid shock over an extended temporal interval that is prohibitively long for untreated rats to learn ( Volle et al, 2016 ). Moreover, in a differential learning paradigm, in which the only one of the two neutral stimuli is paired with eyelid shock, the same manipulation facilitates the formation of differential association without erroneously increasing behavioural responses to the other neutral stimulus ( Jarovi et al, 2018 ). In both studies, the chemogenetic manipulation specifically augmented the duration of oscillatory activity evoked by the shock-predictive stimulus, but not the non-predictive stimulus.…”
Section: Summary Of Available Evidencementioning
confidence: 99%
“…In trace eyeblink conditioning, chemogenetic activation of excitatory neurons in the prelimbic region enables rats to associate a neutral stimulus and eyelid shock over an extended temporal interval that is prohibitively long for untreated rats to learn ( Volle et al, 2016 ). Moreover, in a differential learning paradigm, in which the only one of the two neutral stimuli is paired with eyelid shock, the same manipulation facilitates the formation of differential association without erroneously increasing behavioural responses to the other neutral stimulus ( Jarovi et al, 2018 ). In both studies, the chemogenetic manipulation specifically augmented the duration of oscillatory activity evoked by the shock-predictive stimulus, but not the non-predictive stimulus.…”
Section: Summary Of Available Evidencementioning
confidence: 99%
“…Specifically, during memory recall, the hippocampus (acting as the core of the BIS) is thought to reduce the effects of interference by eliminating competing memories to enable the individual to recall only the correct memory (Gray & McNaughton, 2000). Furthermore, rodent research has identified increased theta synchrony between the medial prefrontal cortex and the hippocampus during memory retrieval (O'Neill, Gordon, & Sigurdsson, 2013) and during the encoding of behaviourally relevant events (Jarovi, Volle, Yu, Guan, & Takehara-Nishiuchi, 2018). Therefore, it is possible that the MF theta, observed here as part of an MF-MPO region pair during goal conflict, is related to the BIS process of resolving conflicts between competing, behaviourally relevant, memories during recall.…”
Section: Theta Coherence Increases Across the Scalpmentioning
confidence: 99%
“…In fact, one hour after training in contextual fear conditioning, the transcription of multiple plasticity-related genes is upregulated in the mPFC, leading to immediate changes in synaptic structure and physiology (Bero et al, 2014). Parallel studies also showed that by enhancing the activity of mPFC neurons during training, it is possible to facilitate the acquisition of hippocampusdependent memories (Benn et al, 2016;Volle et al, 2016;Jarovi et al, 2018;Shibano et al, 2020). These observations, along with earlier findings of impaired hippocampus-dependent memories with disrupted mPFC (Hannesson et al, 2004;Takehara-Nishiuchi et al, 2005;Zhao et al, 2005;Barker and Warburton, 2008;Gilmartin and Helmstetter, 2010;Devito and Eichenbaum, 2011;Gilmartin et al, 2013;Bero et al, 2014), led us to hypothesize that the mPFC may work with, but not follows, the hippocampus to form new memories (Takehara-Nishiuchi, 2020b).…”
Section: Introductionmentioning
confidence: 99%